Multiculturalism, Latin Americans and ‘Indigeneity’ in Australia - Cohen, Erez (The Australian journal of anthropology, 2003)
What are the relations between the discourse of ‘multiculturalism’ and that of ‘indigeneity’ in Australia? In problematising these relations this paper explores the affiliations that Latin American migrants and political refugees living in Adelaide have with the notion of indigeneity. For some Latin Americans affiliations with the struggle of Aboriginal people and indigeneity is a product of strong political identification with the political left and the struggle for human rights in their countries of origin. At the same time references to Latin Americans' indigeneity are often evoked within Australian multicultural settings and performances that promote ‘cultural diversity’ and are consumed by White Australians for their exotic otherness and as forms of cultural enrichment. Such representations work to marginalise further the migrants (and the ‘indigenous’) into a cultural sphere which marks them as the tolerated ethnic ‘Other’.